Initial Reports of the Deep Sea Drilling Project 1984
DOI: 10.2973/dsdp.proc.77.101.1984
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and Explanatory Notes

Abstract: Sample requests should refer to a specific interval within a section of a core, rather than a total depth below sea level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Standard density values were used for continental crust (2.75–2.9 g/cm 3 ), oceanic crust (2.9–3.0 g/cm 3 ), SDRs (2.65–2.75 g/cm 3 ), magmatic underplating (2.9–3.0 g/cm 3 ), serpentinized mantle (2.7–3.2 g/cm 3 ) and mantle (3.3 g/cm 3 ) (Bassetto et al, 2000; Holbrook et al, 1994; Mjelde et al, 2005). In the Eastern Gulf of Mexico, a gravity model was previously applied on the seismic line coincident with the GUMBO line 3 (Liu et al, 2019) using continental crust densities based on the DSDP well Site 537, located on a structural high close to Campeche Escarpment (Buffler, Schlager, Bowdler, et al, 1984; Buffler, Schlager, & Pisciotto, 1984). In this study, we used density values of 2.75 and 2.85 g/cm 3 for the attenuated and thicker continental crust respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard density values were used for continental crust (2.75–2.9 g/cm 3 ), oceanic crust (2.9–3.0 g/cm 3 ), SDRs (2.65–2.75 g/cm 3 ), magmatic underplating (2.9–3.0 g/cm 3 ), serpentinized mantle (2.7–3.2 g/cm 3 ) and mantle (3.3 g/cm 3 ) (Bassetto et al, 2000; Holbrook et al, 1994; Mjelde et al, 2005). In the Eastern Gulf of Mexico, a gravity model was previously applied on the seismic line coincident with the GUMBO line 3 (Liu et al, 2019) using continental crust densities based on the DSDP well Site 537, located on a structural high close to Campeche Escarpment (Buffler, Schlager, Bowdler, et al, 1984; Buffler, Schlager, & Pisciotto, 1984). In this study, we used density values of 2.75 and 2.85 g/cm 3 for the attenuated and thicker continental crust respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These seismic lines partially image the Moho discontinuity; while the basement, syn‐rift and post‐rift sequences are well imaged, where evaporites are not present. Our seismic data were complemented by integrating published seismic interpretations and well data (Buffler, Schlager, Bowdler, et al, 1984; Buffler, Schlager, & Pisciotto, 1984; Marton & Buffler, 1999, 2016) from DSDP leg 77 (site 353; Figure 1). These data are located to the southeast of our study area and were used to correlate the top syn‐rift sequence previously identified in DSDP leg 77, site 535 (Buffler, Schlager, Bowdler, et al, 1984; Buffler, Schlager, & Pisciotto, 1984; Marton & Buffler, 1999, 2016) into our seismic reflection lines and construct the structural framework at the south‐western part of the Florida margin.…”
Section: Data and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a). assessed the stratigraphic structure of the seabed was from seismograms and core data [Buffler et al (1984); Worzel (1973); Shaub (1987); Brunson et al (1980)]. Fig.…”
Section: Modeling Of 3d Propagation Effects Observed In the Church Stmentioning
confidence: 99%